Evaluating organic acids as alternative leaching reagents for metal recovery from lithium ion batteries. (15th June 2019) - Musariri, Bruce; Akdogan, Guven; Dorfling, Christie; Bradshaw, Steven
Highlights: Citric acid is effective as lixiviant for metal recovery from lithium ion batteries. >95% Co, Li and Ni dissolution achieved with 1.5 M citric acid at 95 °C. Addition of H2 O2 as reductant significantly increased leaching rates. Abstract: Recycling of lithium ion batteries (LIBs) is important from an environmental management perspective and because of the potential economic benefits associated with the recovery of scarce resources such as lithium and cobalt. Current hydrometallurgical metal recycling processes involve dismantling and size reduction followed by leaching with mineral acids; these lixiviants present an environmental challenge of its own. This project evaluated the technical feasibility of using organic acids, which potentially have a smaller environmental impact that mineral acids, as lixiviants to recover lithium, cobalt and nickel from LIBs. Batch atmospheric leaching tests were performed with citric acid and DL-malic acid to investigate the effect of acid concentration, leaching temperature and H2 O2 addition on metal leaching. Leaching with 1–1.5 M citric acid and 2 vol% H2 O2 at 95 °C achieved more than 95% Co and Li dissolution; these results suggest that organic acids can possibly substitute inorganic acids as environmentally friendly lixiviants.